Family-Friendly Solutions in Personal Income Tax in Poland in the Context of Modern Demographic Trend - Lewkowicz-Grzegorczyk, Katarzyna (Journal of Finance and Financial Law, 2024)
The purpose of the article. The aim of the article is to assess the importance of family-friendly solutions in PIT aimed at supporting families with children in Poland against the background of EU countries in the context of contemporary demographic challenges. Research hypothesis. Income tax relief and exemptions are one of the most important tax instruments of family policy in Poland. Methodology. A descriptive and comparative analysis method was used to achieve the research objective. Data from 2009–2021 on tax preferences and the number of taxpayers benefiting from them were mainly sourced from the MF and the CSO’s BBGD. The results of a CBOS survey were also used to assess family support solutions in Poland. Results of the research. Tax preferences, including child allowances, are one of the most common solutions reached by most EU countries to create conditions for improving fertility rates. Based on the analysis, it was concluded that the changes in the construction of the child tax allowance in Poland, in force since 2014, have made it a strong instrument of support, especially for families with many children and low income. The introduced changes increase the effectiveness of this preference as a redistribution tool and are at the same time assessed as more socially just. Although the modified allowance increased the amount of PIT refunds to families, it did not contribute at all to improving fertility rates, as did the benefits under the “Family 500+”programme. In 2021, the fertility rate (TFR) for Poland oscillated around the value of 1.33, i.e. at an extremely low level.